(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Buckwheat research has been carried out within the long-term crop rotation stationary that was established in 1969 as a part of the Research institute of Agriculture. Buckwheat proportion within the partcular crop rotations went up to 22%. The highest buckwheat yields were obtained from the buckwheat variants that where cultivated after winter rye, and within the buckwheat monoculture experimental plots. A considerable yield decrease was observed when cultivating buckwheat after potatoes. Weeds in the buckwheat sowing were effectively brought under control by the herbicide Butisane 400 (1.5 l ha-1), applied immediately after sowing and Betanal AM 2.5 l ha-1 after seedling in 2-3 leaves stage.